Characterising TOI-732 b and c: new insights into the M-dwarf radius and density valley - Bonfanti, Andrea; Brady, M.; Wilson, T. G.; Venturini, J.; Egger, J. A.; Brandeker, A.; Sousa, S. G.; Lendl, M.; Simon, A. E.; Queloz, D.; Olofsson, G.; Adibekyan, V.; et al. (Astronomy and astrophysics, 2024)
Context. TOI-732 is an M dwarf hosting two transiting planets that are located on the two opposite sides of the radius valley. Inferring a reliable demographics for this type of systems is key to understanding their formation and evolution mechanisms. Aims. By doubling the number of available space-based observations and increasing the number of radial velocity (RV) measurements, we aim at refining the parameters of TOI-732 b and c. We also use the results to study the slope of the radius valley and the density valley for a well-characterised sample of M-dwarf exoplanets. Methods. We performed a global Markov chain Monte Carlo analysis by jointly modelling ground-based light curves and CHEOPS and TESS observations, along with RV time series both taken from the literature and obtained with the MAROON-X spectrograph. The slopes of the M-dwarf valleys were quantified via a support vector machine (SVM) procedure. Results. TOI-732b is an ultrashort-period planet (P = 0.76837931-0.00000042+0.0000039 days) with a radius Rb = 1.325-0.058+0.057R⊕, a mass Mb = 2.46 ± 0.19 M⊕, and thus a mean density ρb = 5.8-0.8+1.0 g cm-3, while the outer planet at P = 12.252284 ± 0.000013 days has Rc = 2.39-0.11+0.10R⊕, Mc = 8.04-0.48+0.50M⊕, and thus ρc = 3.24-0.43+0.55 g cm-3. Even with respect to the most recently reported values, this work yields uncertainties on the transit depths and on the RV semi-amplitudes that are smaller up to a factor of ~1.6 and ~2.4 for TOI-732 b and c, respectively. Our calculations for the interior structure and the location of the planets in the mass-radius diagram lead us to classify TOI-732 b as a super-Earth and TOI-732 c as a mini-Neptune. Following the SVM approach, we quantified d log Rp,valley / d logP = -0.065-0.013+0.024, which is flatter than for Sun-like stars. In line with former analyses, we note that the radius valley for M-dwarf planets is more densely populated, and we further quantify the slope of the density valley as d log ρ^valley / d log P = -0.02-0.04+0.12. Conclusions. Compared to FGK stars, the weaker dependence of the position of the radius valley on the orbital period might indicate that the formation shapes the radius valley around M dwarfs more strongly than the evolution mechanisms.
Online veröffentlicht: 06. Februar 2024
Gesehen am 07.08.2024